CHALLENGES AND RISKS FACING THE RENOVATION OF TRANSPORT AND MILITARY INFRASTRUCTURE IN THE RUSSIAN ARCTIC ZONE - I. Frolov (Модернизация, инновация, развитие, 2016)
This paper analyzes the resumption of works aimed at rebuilding and modernizing transport and related military infrastructure in the Russian part of the Arctic. The analysis of the category of «risk». The objective of linking various state programs involved in the research and development of the Arctic is formulated in view of various types of risks a tree of objectives assigned to these programs in the context of uncertain changes in the timeline and volume of funding allocated for diff erent programs.